Dimensões formativas da phronesis aristotélica - Guisso, Mariana de Oliveira (2019)
The present dissertation aims to explore the formative dimensions of the Aristotelian phronesis (prudence), understanding as a practical rationality that can help to think about the educational field in a large way. The research problematic is translate in the following question: What is the formative sense of the Aristotelian phronesis? According to this line of thought, we discourse about how it is possible to think the Aristotelian phronesis as a prudential and educational rationality able to potentially contribute with a more large perspective of human formation. This work has as methodology the bibliographic research interpreting the Aristotle's concept of phronesis in a hermeneutic perspective based in the Ética a Nicômacos. In the first moment, we revisit some essentials previous aspects to the Aristotelian phronesis's understanding, and in order to do so, we explain the mains characteristics of Eudaimonia and the moral virtue. In a second moment is present the concept of phronesis from book VI of Ética a Nicômacos and its dismemberment in the Aristotelian moral theory. Finally, in the third moment, we discuss the relation between the prudential rationality and the educational field, sought discourse phronesis formative dimensions. Through the present dissertation, we are able to realize that the Aristotelian phronesis has an intrinsic connection with the educational field when are investigated the formation dimensions. We conclude that the phronesis, as prudential rationality that is, guides the human activity inside a world of the possible, marked for the contingency and the fragility of the good as characteristics of the human condition. While practical rationality, the phronesis links the human formative dimensions according to as articulate the cultivation of the good life, the virtues and the habits and, as practical knowledge, encourage a relation with the pedagogical knowledge to more than just epistemic dimensions.